STYLISTIC DEVICES AND ROYAL IMAGERY IN HAUSA PRAISE POETRY: A LINGUISTIC ANALYSIS OF ADAM A. ZANGO’S WAƘAR SARKIN ZAZZAU - Shuaibu, A; Uba, A (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2025)
This paper investigates the stylistic and cultural meaning of Waƙar Sarkin Zazzau, one of the royal praises composed by the renowned Kannywood recordist Adam A. Zango. This paper presents a qualitative analysis of the lyrics on stylistic and ethnographic levels and asks how language is mobilized to create authority, identity, and reverence in accordance with Hausa sociopolitical tradition. Some of the most important features of linguistics, such as metaphor, repetition, diction, and symbolism, are dissected. The results indicate that the imagery (motifs) used by Zango (such as lion, drum of elephants skin, and sign of hunter) introduces the Emir as a symbol of human strength, religious authority, and cultural authority. Repetition and parallelism enhance the rhythm and rhetoric effect of the song, strengthening the sense of admiration and ideological reverence. The paper concludes that the stylistic features of Hausa praise poetry are not just esthetic ones; however, they have an intense ideological load, which supports the old regime of power and community memory. Future research directions, such as a comparative study with traditional ganga praise poetry, stylistic change in contemporary Kannywood music, and cross-cultural studies between the Yoruba and Igbo genres of praise, have been recommended. This study contributes to knowledge of the relationship between language and power in African oral literature and the study of Hausa stylistics, discourse analysis, and indigenous musical styles